Pengaruh Tingkat Pengetahuan Agama terhadap Persepsi Mahasiswa pada Gerakan Radikalisme Berbasis Agama (Studi pada Mahasiswa UIN Raden Intan Lampung) - Syafe'i, Imam (Universitas Islam Negeri Raden Intan Lampung, 2018)
The main objective in this study was to determine the effect of the level of religious knowledge on student perceptions of religious-based radicalism movements. This type of research is survey research using quantitative research methods. The population is fifth semester students at Raden Intan Lampung State Islamic University 2017/2018 academic year with a sample of 295 students. The technique of collecting data uses questionnaires and documents. The data that has been obtained is then analyzed using a simple linear regression test. The conclusion of the study is that the research hypothesis is not accepted, so the level of religious knowledge does not have a significant effect on student perceptions of religious-based radicalism. The magnitude of the influence of religious knowledge on student perceptions of religious-based radicalism is only 1.7% which is categorized as very weak influence.